PENGARUH CONSCIENTIOUSNESS TERHADAP SOCIAL LOAFING MAHASISWA DALAM BEKERJA KELOMPOK - Nur’aini; Gazi Saloom (Qiro'ah : Jurnal Pendidikan Agama Islam, 2024)
This study aims to examine the extent to which conscientiousness is a predictor of student social loafing through the mediator variable interpersonal relationships. The sample of this study amounted to 414 students. Sampling using convenience sampling. This research uses quantitative methods, the research data is analyzed by path analysis with the help of MPLUS software. The results showed that the model fit the data, had a negative coefficient direction (-). The significance of the direct effect of conscientiousness on student social loafing is indicated by the t-value (-12.711) and the indirect effect of (-6.644). This means that the higher or the greater the number of group members with conscientiousness personality mediated by interpersonal relationships, the smaller the social loafing in doing group assignments. Thus the mediator variable functions well. Therefore, further research is recommended to examine the dimensions of the Big Five Personality using the same variables in order to add insight and be able to find differences between personality dimensions. In addition, it is expected to control the type of task and the unclear division of responsibilities.